2018
DOI: 10.1016/j.juro.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Women Undergoing Third Line Overactive Bladder Treatment Demonstrate Elevated Thermal Temporal Summation

Abstract: Purpose To determine if women with overactive bladder (OAB) requiring 3rd line therapy demonstrate greater central sensitization, indexed by temporal summation to heat pain stimuli, than those with OAB. Materials and Methods We recruited 39 adult women with OAB from the Urology clinic who were planning to undergo interventional therapy for medication refractory OAB with either onabotulinumtoxinA bladder injection or sacral neuromodulation and 55 women with OAB, either newly seen in our Urology clinic or resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The current study focuses on thermal TS, which typically involves the delivery of a set of identical, noxious heat pulses to the body via a thermode. Thermal TS can be delivered in a standardized fashion, is generally well tolerated, and has been widely studied 4,612…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on thermal TS, which typically involves the delivery of a set of identical, noxious heat pulses to the body via a thermode. Thermal TS can be delivered in a standardized fashion, is generally well tolerated, and has been widely studied 4,612…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually it is possible that the systemic cluster might have “top-down” or systemic mechanisms such as central sensitization, systemic inflammation, or psychosocial trauma. Central sensitization has recently been demonstrated in some OAB patients by Reynolds et al [ 8 , 9 ]. In future studies it is important to study the differences in pathophysiology among the OAB subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al have shown that patients requiring third line treatment for OAB (“refractory” patients) demonstrated higher rates of central sensitization when compared to patients who were first presenting for OAB treatment (treatment naïve) [ 9 ]. This observation lends credence to our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A standardized oscillating heat pain stimulation protocol (Medoc TSA 2001, Minneapolis, MN) was used to determine temporal summation, similar to our previous work. 40 , 43 A sequence of 10 heat pulses, 0.5 seconds in duration, with a 35°C base temperature, an intertrial interval of 2.5 seconds, and 50°C target stimulus intensity was applied to the left volar forearm. Participants were asked to provide verbal numeric pain ratings (0 = “no pain” to 100 = “most pain possible”) immediately after the peak of each pulse.…”
Section: Methodsmentioning
confidence: 99%